PENGARUH PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP PENINGKATAN BRAND IMAGE, CORPORATE REPUTATION SERTA CUSTOMER LOYALTY PADA BANKALTIMTARA - Rahmatussani, Andi Mahardiyanti; Hudayah, Syarifah; Rahmawati, Rahmawati (FEB Universitas Sam Ratulangi Manado, 2020)
Abstract : The purpose of this study was to determine how the influence of Bankaltimtara's CSR Program on brand image, corporate reputation and customer loyalty at Bankaltimtara Company. The research was conducted by taking the object of Bankaltimtara customers using hundred respondents obtained from the number of bank accounts of Bankaltimtara conventional customers. As for the data analysis used by the author is using statistical test tools, namely the Structural Equation Model (SEM) test with the alternative method of Partial Least Square (PLS) using the SmartPLS 3.0 software. Hypothesis testing is done by multivariate analysis, which runs through the PLS program. Data analysis through Partial Least Square (PLS) was carried out in two stages, namely: First, assessing the outer model or measurement model. Second, assessing the inner model or structural model. The results of the assessment indicate that there is a significant influence between Bankaltimtara's CSR Programs on Bankaltimtara's brand image and corporate reputation, but it has no effect on Bankaltimtara's customer loyalty. Meanwhile, for Bankaltimtara brand image, it has a significant effect on Bankaltimtara's corporate reputation and customer loyalty. So CSR Program should be developed in line with the development of product due to customer’s need in order to meet customer loyalty. Abstrak: Tujuan penelitian ini adalah untuk mengetahui bagaimana pengaruh Program CSR Bankaltimtara terhadap brand image, corporate reputation serta customer loyalty pada Perusahaan Bankaltimtara. Penelitian dilakukan dengan mengambil obyek nasabah Bankaltimtara dengan menggunakan 100 responden dari jumlah akun rekening nasabah Bankaltimtara konvensional. Adapun analisis data yang digunakan oleh penulis adalah menggunakan alat uji statistik yaitu dengan uji Model Persamaan Struktural Structural Equation Model (SEM) dengan metode alternatif partial least square (PLS) menggunakan software SmartPLS 3.0.. Analisis data melalui Partial Least Square (PLS) dilakukan melalui dua tahap, yaitu : Pertama, Menilai outer model atau model pengukuran. Kedua, menilai inner model atau model struktural. Hasil penilaian menunjukkan bahwa terdapat pengaruh yang signifikan antara Program CSR Bankaltimtara terhadap brand image dan corporate reputation Bankaltimtara, namun tidak berpengaruh terhadap customer loyalty Bankaltimtara. Sedangkan untuk brand image Bankaltimtara, memiliki pengaruh yang signifikan terhadap corporate reputation dan customer loyalty Bankaltimtara. Sehingga perlunya pengembangan Program CSR yang seiring dengan pengembangan produk yang dapat menjawab segala kebutuhan nasabah untuk lebih meningkatkan loyalitas nasabah Bankaltimtara. Corporate Social Responsibility, Brand Image, Corporate Reputation